Housing Associations as institutional space: Care and control in tenant welfare and training for work. Issue 2 (2nd July 2018) - Wainwright, Emma; Marandet, Elodie
Abstract : Housing Associations (HAs) operate at the community level between the state, market and individual and, in the current political context of austerity, state roll‐back and welfare reform, have been increasingly tasked with focusing on the "welfare" of their tenants. This has included "encouraging" a trajectory of training for work for those tenants who are unemployed; a trajectory that is aimed at producing a certain type of "active" and appropriate citizen‐tenant at the local level and that is based on the problematisation of those in social housing. This paper concentrates on how this trajectory is mobilised and implemented with an emphasis on how we conceptualise the dynamics and complexities of care and control that are central to this. HAs are framed as important locally‐based institutions tasked with the local enactment of national policy imperatives. Through training‐for‐work initiatives, we explore how tenants are marked through the physical and conceptual spaces operated by HAs, and how HAs act as intermediaries between wider policy imperatives and localised, place‐specific and embodied interactions between tenants and housing professionals. We reflect on the dynamics of care and control involved in tenant engagement, with "care" couched in terms of support and empathy but prompted by systems of control that classify and mark out tenants as in most "need." We highlight the important role of HAs as fluid institutional sites of connection, emphasising the embodied and spatial regulatory relations through which careful control is enacted and practised.